Free market reform and drug market prohibition : US policies at cross-purposes in Latin America. - ANDREAS, Peter (1995)
Examines how the drug trade has both facilitated and been encouraged by the IMF-style programmes to remedy the debt crisis and balance of payments problems of Peru and Bolivia. Concludes that contra-indications between market liberalisation and drug market prohibition are obscured by Washington policy debate.